Issues at the Rural-Urban Fringe: Florida's Population Growth, 2004-2010 - Rodney L. Clouser; Hank Cothran (EDIS)
State population increases will impact and influence water and land allocation, state and community infrastructure needs, and demands for local goods and services. Therefore, data presented in this fact sheet can serve as a useful introduction of issues related to population growth that might arise over the next six years in Florida. The data will explain where the state's growth will occur, but also may help identify where issues such as water and land competition, housing demand, consumer demand for goods and services, urban sprawl, changes in rural and farm land use, etc. will become increasingly important. These specific issues are not addressed in this fact sheet but left to the conjecture of the reader based on the data presented.  This is EDIS document FE567, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida, Gainesville, FL. This document is one of a series entitled "Issues at the Rural-Urban Fringe". Published August 2005.